The role of FAM171A2-GRN-NF-κB pathway in TBBPA induced oxidative stress and inflammatory response in mouse-derived hippocampal neuronal HT22 cells - Yi Wang; Jing Shan; Ling Zhang; Rui Wang; Meng-Yu Wu; Hong-Mei Li; Hai-Ming Xu (Ecotoxicology and Environmental Safety)
Tetrabromobisphenol A (TBBPA) is one of the brominated flame retardants (BFRs) widely used in industry, which has a broad toxic effect on organisms. However, there is still limited research on the neurotoxic mechanism of TBBPA. Using mouse hippocampal neurons (HT22) cells, the toxicity of TBBPA was evaluated, especially focusing on its alteration on the key molecules in FAM171A2-GRN-NF-κB signaling pathway. The results showed that TBBPA exposure could lead to an increase in the production of inflammation-related genes IL-6, iNOS, TGF-β1, COX2, and TNF-α in both HT22 cells and HT22-AD-model, intensifying the inflammatory response; it inhibits the mRNA expression of antioxidative enzymes genes Sod1, Cat, Gpx1, and Gsta1, resulting in reduced antioxidant enzyme activities of SOD, CAT, and GSH-Px/GPX. Mechanistically, TBBPA caused the upregulation of FAM171A2 expression level, alongside increased GRN, IκBα and p65 levels; whereas the expression of GRN, IκBα and p65 was decreased after FAM171A2 knockdown, demonstrating TBBPA-induced upregulation of FAM171A2 should be responsible for the increased GRN, IκBα and p65 expression. Therefore, for the first time, our data indicate that TBBPA-induced oxidative stress and inflammatory response is closely related to the FAM171A2-GRN-NF-κB pathway.